2012
DOI: 10.1007/s11357-012-9401-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the transition to mid-life in Caenorhabditis elegans

Abstract: We present an initial molecular characterization of a morphological transition between two early aging states. In previous work, an age score reflecting physiological age was developed using a machine classifier trained on images of worm populations at fixed chronological ages throughout their lifespan. The distribution of age scores identified three stable post-developmental states and transitions. The first transition occurs at day 5 post-hatching, where a significant percentage of the population exists in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…In agreement with our hypothesis that the induction of these genes can be considered as an indication of advanced senescence, published transcriptome analysis of the aging C. elegans showed that the expression of heat-shock protein genes increased after the reproductive period, even at 20°C (Eckley et al, 2013;Lund et al, 2002). On the other hand, genes coding for the transcription factors DAF-16 and HSF-1 were more expressed in the fast than in the slow category.…”
Section: High Transcript Levels Of Genes Coding For Small Heat-shock supporting
confidence: 87%
See 1 more Smart Citation
“…In agreement with our hypothesis that the induction of these genes can be considered as an indication of advanced senescence, published transcriptome analysis of the aging C. elegans showed that the expression of heat-shock protein genes increased after the reproductive period, even at 20°C (Eckley et al, 2013;Lund et al, 2002). On the other hand, genes coding for the transcription factors DAF-16 and HSF-1 were more expressed in the fast than in the slow category.…”
Section: High Transcript Levels Of Genes Coding For Small Heat-shock supporting
confidence: 87%
“…A useful biomarker must be a better predictor of lifespan than chronological age. Different biomarkers have been used to determine biological age of C. elegans nematodes: accumulation of lipofuscin in the gut, rate of pharyngeal pumping, pharyngeal morphology, defecation rates, internal growth of food bacteria, ability to induce heat-shock response, induction of certain genes (e.g., sod-3), and muscle-function decline that results in reduction of motility with age (Eckley et al, 2013;Pincus and Slack, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…4 G-I). Accelerated aging was also found when using a machine classifier to quantify morphological changes that occur with aging in the head of nematodes (32)(33)(34) (Fig. 4J).…”
Section: Stabilization Of G4 Structures Leads To Accelerated Agingmentioning
confidence: 83%
“…We previously showed that pharynx muscle morphology reflects the aging state of the whole organism, and based on this mechanism in combination with machine-learning software, we analyzed the effects of tomatidine on age stage scoring of pharynx in accordance to the previous publications3536. We defined C. elegans pharynx scoring from stage 0 (young) to stage 3 (old): stage 0  C. elegans are predominantly found in the first 2 days of adulthood and are developing fecundity.…”
Section: Resultsmentioning
confidence: 99%